PENGARUH MEDIA SOSIAL, KEPERCAYAAN KONSUMEN DAN KUALITAS E-SERVICE TERHADAP NIAT BELI KONSUMEN DI TERMINAL JATIJAJAR - Andry Ardiansyah; Yenita (GoAcademica Research dan Publishing, 2023)
This study to analyze the influence of social media, consumer trust and service quality on consumer purchase intentions at the Jatijajar Terminal. This research method uses quantitative data collection methods by distributing questionnaires to passengers. The data collection method is through questionnaires which are distributed directly to passengers as many as 50 respondents. Based on the results of this study, it is explained that E-Service, Customer Trust has a significant effect on consumer purchase intentions at Terminal Type A Jatijajar, Depok city, then Social-Media has no effect on consumer purchase intentions at Terminal Jatijajar. Meanwhile, social media has no effect on consumer purchase intentions at the Jatijajar Terminal. Therefore, Jatijajar Terminal is deemed necessary to improve services on social media variables so that consumer buying intentions also increase. The results of this study can be used as a reference for further research.